PREVIOUS CONVICTION AS A DISCRIMINATORY EMPLOYMENT CONDITION - Obradović, Goran; Tasić, Anđelija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
"Looking for a female worker to work in a bakery" or "Send a CV with a picture" are prototypes of advertisements that are typical examples of direct discrimination when establishing an employment relationship. The competent institutions reacted to such and similar advertisements and the citizens’ awareness grew to such an extent that they, in the form of the so-called testers, organized to gather evidence to establish that one conduct constitutes an act of discrimination. With that in mind, the authors are wondering why some other personal characteristics, sometimes required from a candidate for employment, do not cause revolt and are almost considered desirable. How it is possible that even state authorities can ask the candidate for confirmation that he/she has not been convicted or that no legal proceeding is being conducted against him/her? Is it crutial for the job of a nurse - medical technician whether a person has been convicted of some of the crimes against road safety? In what way does the state provide the possibility of resocialization of convicts if it, before others, for jobs in the public sector, requires this type of certificate, indiscriminately to the type of criminal offences and the length of the sentence imposed? Finally, what about the presumption of innocence, one of the basic postulates of criminal procedure? By analyzing the current legal regulations and the practice of independent bodies and international institutions, the authors try to answer to these and other questions that have been raised in the paper.
Keywords: working relationship; discrimination; conviction